2018
DOI: 10.1002/tea.21515
|View full text |Cite
|
Sign up to set email alerts
|

Self‐beliefs in organic chemistry: Evaluation of a reciprocal causation, cross‐lagged model

Abstract: This study is designed to test a reciprocal causation, cross‐lagged model of self‐concept, self‐efficacy, and achievement in a postsecondary STEM course. Both self‐efficacy and self‐concept are known to be related to achievement; however, there is a need to untangle the relationship between the two constructs as well as their association to achievement across time to best direct future research efforts. To achieve this research interest, a longitudinal measurement strategy was used to measure chemistry self‐co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 93 publications
(180 reference statements)
0
22
0
Order By: Relevance
“…Structural equation modeling (SEM) is a suitable method to explore the relationship between attitude toward chemistry and achievement measures such as exam scores . Five models were tested (A–E) for the students in the flipped classroom using a reciprocal causation framework drawn from control-value theory. The best fitting model (A), both statistically and theoretically, was chosen to explain the relationships among the variables. Figure displays model A, while Figure S3 and Table S6 in the Supporting Information show models A–E and their respective fit statistics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural equation modeling (SEM) is a suitable method to explore the relationship between attitude toward chemistry and achievement measures such as exam scores . Five models were tested (A–E) for the students in the flipped classroom using a reciprocal causation framework drawn from control-value theory. The best fitting model (A), both statistically and theoretically, was chosen to explain the relationships among the variables. Figure displays model A, while Figure S3 and Table S6 in the Supporting Information show models A–E and their respective fit statistics.…”
Section: Methodsmentioning
confidence: 99%
“…While the techniques that are demonstrated in this report can be applied to any student population in any discipline for a variety of different constructs, the present study focuses on Black female students’ attitudes toward chemistry in a first semester organic chemistry course. Additionally, we examine the relationship between attitude and achievement and explore the feasibility of a reciprocal causation model between attitude toward chemistry and subsequent exams at the beginning and end of the semester. From the control-value theory (CVT) perspective, achievement emotions, which include affective, cognitive, motivational, expressive, and peripheral physiological processes, are directly linked to achievement activities and outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Flaherty found that the strong majority of research on student attitudes has focused on comparing a dimension of attitude among student groups, to assess the impact of a learning intervention on student attitude or relating student attitude to academic performance. The latter grouping has demonstrated the important role of attitude in student learning as student attitude accounts for a proportion of academic performance even when accounting for past academic performance. Despite the importance of student attitude within the chemistry class setting, Flaherty describes a dearth of research evaluating efforts to improve student attitude characterizing prior work as interventions designed primarily to promote learning instead of attitude . SPIs offer an opportunity to address this gap in the research literature as they are purposely designed to impact student attitude.…”
Section: Growth Mindset Interventionmentioning
confidence: 99%
“…Some prior administrations of the CSCI have indicated that, in order to obtain satisfactory data-model fit in CFA, some correlated errors were required, in part due to the covariance resulting from having negatively worded items in the scale that tend to cluster together. 88 In this study, CFA was performed using MPlus version 8.5 and resulted in an acceptable data-model fit after dropping one item from the scale and allowing the negatively worded items to covary (CFI = 0.968, TLI = 0.932, SRMR = 0.038, RMSEA = 0.090). The CFA results are included in the Supporting Information.…”
Section: Chemistry Self-concept Inventorymentioning
confidence: 99%